1978
DOI: 10.1093/nar/5.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Thermal denaturation of nucleosomal core particles

Abstract: Thermal denaturation of very homogeneous preparations of core particles from chicken erythrocyte chromatin is studied by several techniques. The change in absorbance, which is very closely paralleled by changes in heat capacity, is a biphasic process with inflexions at 600C and 740C. In contrast, isolated DNA of the same length denatures in a single transition around 440C. Monitoring the circular dichroism of the cores during thermal denaturation reveals biphasic changes in the secondary structure of the DNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
125
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(157 citation statements)
references
References 40 publications
31
125
1
Order By: Relevance
“…The heats of the transitions are reported in Table 1. These data are in close agreement with those reported by Weischet et al (10). These authors showed that these transitions roughly parallel those observed optically, and suggested that the low-temperature transition corresponds primarily to the melting of about 40 base pairs of DNA from the ends of the core particles.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…The heats of the transitions are reported in Table 1. These data are in close agreement with those reported by Weischet et al (10). These authors showed that these transitions roughly parallel those observed optically, and suggested that the low-temperature transition corresponds primarily to the melting of about 40 base pairs of DNA from the ends of the core particles.…”
Section: Methodssupporting
confidence: 92%
“…We have shown previously (6) that core particles with crosslinked histone cores exhibit a low-temperature optical transition similar to that of native core particles but that the main transition is shifted to a higher temperature. This is consistent with fraying of DNA from the ends of the particle and a strong coupling of the stability of the central region of the DNA to the stability of the histone octamer, as postulated for native core particles (10,11). Therefore, it is of interest to compare the enthalpy change for denaturation of fully folded crosslinked particles with that found for partially unfolded native particles.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…Perhaps the entire complement of DNA within the particle behaves in this way, but it is also possible that only a certain fraction, near the ends, can break loose from the surface of the core particle so that it effectively becomes part of the linker DNA (see for example refs. [13][14][15]. Our results would then suggest that the portion of DNA remaining bound to the core must have an average superhelix density close to -0. superhelix density averaged over 230 bp is about -0.046.…”
Section: Resultsmentioning
confidence: 95%
“…In this model there can be interaction of DNA in one core (18), that amounts up to 20 bp at each end could be so loosened.…”
Section: Discussionmentioning
confidence: 99%